The care and feeding of ravenously hungry girls - Gray, Anissa (Berkley, 2019)
The Butler family has had their share of trials<U+2014>as sisters Althea, Viola, and Lillian can attest<U+2014>but nothing prepared them for the literal trial that will upend their lives. Althea, the eldest sister and substitute matriarch, is a force to be reckoned with and her younger sisters have alternately appreciated and chafed at her strong will. They are as stunned as the rest of the small community when she and her husband Proctor are arrested, and in a heartbeat the family goes from one of the most respected in town to utter disgrace. The worst part is, not even her sisters are sure exactly what happened. As Althea awaits her fate, Lillian and Viola must come together in the house they grew up in to care for their sister<U+2019>s teenage daughters. What unfolds is a stunning portrait of the heart and core of an American family in a story that is as page-turning as it is important.